What doctors think about the impact of managed care tools on quality of care, costs, autonomy, and relations with patients - Bovier Patrick A; Agoritsas Thomas; Deom Marie; Perneger Thomas V (BMC, 2010)
Abstract Background How doctors perceive managed care tools and incentives is not well known. We assessed doctors' opinions about the expected impact of eight managed care tools on quality of care, control of health care costs, professional autonomy and relations with patients. Methods Mail survey of doctors (N = 1546) in Geneva, Switzerland. Respondents were asked to rate the impact of 8 managed care tools on 4 aspects of care on a 5-level scale (1 very negative, 2 rather negative, 3 neutral, 4 rather positive, 5 very positive). For each tool, we obtained a mean score from the 4 separate impacts. Results Doctors had predominantly negative opinions of the impact of managed care tools: use of guidelines (mean score 3.18), gate-keeping (2.76), managed care networks (2.77), second opinion requirement (2.65), pay for performance (1.90), pay by salary (2.24), selective contracting (1.56), and pre-approval of expensive treatments (1.77). Estimated impacts on cost control were positive or neutral for most tools, but impacts on professional autonomy were predominantly negative. Primary care doctors held more positive opinions than doctors in other specialties, and psychiatrists were in general the most critical. Older doctors had more negative opinions, as well as those in private practice. Conclusions Doctors perceived most managed care tools to have a positive impact on the control of health care costs but a negative impact on medical practice. Tools that are controlled by the profession were better accepted than those that are imposed by payers.